Differentiated Thyrod Malignancies - Sulaiman, Tharwat I. (Journal of the Faculty of Medicine Baghdad, 2005)
Thyroid cancer is a rare malignancy with wide interethnic and geographic variations (l).it constitutes 1% of solid organ malignancy (2) but they are still the most common endocrine (3)cancer .well differentiated (follicular and papillary thyroid carcinoma accounts for 80-90% of the approximately 28000 new cases each year and the estimate of 376000 existing cases of primary thyroid cancer in Europe and united states(2) , while in Germany it is the 13th most frequent maiignancy(2-7) new cases per 100000 inhabitantsK 1)-There have been many recent advances in our understanding of thyroid diseases. An adenoma- carcii.oma sequence for the development of thyroid neoplasm has been based on the characterization of a number proto-oncogene and tumour suppressor gene, and different pathways for the development of papillary and follicular thyroid carcinoma have been demonstrated (5).Over the past several decades, iodides supplementation to food supplies in many parts of the world has been followed by a correspondence decrease in the incidence . of follicular thyroid carcinoma (4).The mean survival rates in papillary thyroid cancer usually exceed 90%, whereas in follicular thyroid cancer they amount to approximately 80% (1). For that reason differentiated thyroid cancer is considered among the most curable neoplasm (3).The prognostic factors for papillary thyroid carcinoma are distant metastasis, age and extra thyroidal growth, and for follicular carcinoma they are distant metastasis, extra thyroidal extension and multifoccal growth Also in follicular carcinoma , survival is significantly influenced by some of the clinical variables , particularly loco regional extension of the disease and patients age (6,7,8).The union international contre Le cancer and European organization for research and treatment score and the age , grade , extent and size scores are all highly significant(6,7).on the other hand .Hormones, sex and lymph node metastasiss are not considering prognostic factors for survival (7).A comprehensive study in Japan on 327- patients with thyroid carcinoma showed that in papillary carcinoma there is a difference in thtee survival between young (less than 45 years of age:))and old patients ( 45 years of age or older ). THk rate of patients who died of thyroid cancer also increased in cases with extra thyroidal tissue invasions, and metastasis to distant organs (7).